Viceroy butterfly Limenitis archippus (Cramer) (Lepidoptera: Nymphalidae: Limenitidinae) - Andrei Sourakov (EDIS, 2009)
EENY-458, a 5-page illustrated fact sheet by Andrei Sourakov, is part of the Featured Creatures collection. It describes this black butterfly with white vertical stripes, which is similar to, but smaller than, the monarch butterfly — its synonymy, distribution, description, life cycle, hosts, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, June 2009.